Assessment of Factors Affecting Agricultural Soil Damage in the Upper Stream Sub-Watershed - Velian Sandy Wardana; Bistok Hasiholan Simanjuntak (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Soil damage can be caused naturally or by human activities. Potential areas that have high soil damage are sub-watershed areas and one of them is the Upper Serang Sub-watershed in Central Java. Assessment of potential and actual land damage will help to make wise land use planning. This research aims to assess actual and potential soil damage and the factors affecting the Upper Serang Sub-watershed. This research used descriptive quantitative and qualitative methods, where quantitative descriptive methods were used to assess soil damage and descriptive qualitative methods were used to determine farmer activity factors about soil conservation. The research result, that potential soil damage was included in the highly class soil damaged category with limiting factors are high rainfall of around > 2500 mm/year, slopes that exceed 25% (25-40% and >40%), soil type was dominated by Inceptisol soil and land use dominated by the moor. Meanwhile, actual soil damage has a slightly soil-damaged class with the limiting factors being permeability, redox potential, and the combined permeability and the soil fraction composition. Actual soil damage has a slightly soil-damaged class (RI) because farmers have taken soil conservation measures by mechanical methods dominant. Future efforts that farmers must do are to increase soil conservation measures with a combination of mechanical and biological conservation methods. Keywords: Actual soil damage, Potential soil damage, Upper Serang Sub-watershed.